Successful control of COVID-19 outbreak through tracing, testing, and isolation: Lessons learned from the outbreak control efforts made in a metropolitan city of South Korea - Seung-Ji Kang; Sooyeon Kim; Kyung-Hwa Park; Sook In Jung; Min-Ho Shin; Sun-Seog Kweon; Hyang Park; Seong-Woo Choi; Eungyu Lee; So Yeon Ryu (Elsevier, 2021)
The first surge of coronavirus disease 2019 (COVID-19) cases began on June 27, 2020 in Gwangju metropolitan city, located in the southwestern part of South Korea, with a population of 1,501,000. Local governments and the Korean Center for Disease Control and Prevention immediately started an epidemiologic investigation and traced the contacts of patients using a wide variety of data sources, including location data from mobile devices, credit card transaction, and closed-circuit television footage. Until July 16, 2020, 138 community transmission cases and 10 infection clusters were identified across the city. Through contact tracing, epidemiologic relatedness was found in 136 (98.6%) of 138 cases. Our investigation showed how the extensive and meticulous contact tracing suppressed COVID-19 outbreak in a populated city.